PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ATURAN PENCACAHAN DI KELAS XII MIA 1 SMA NEGERI 1 SIRENJA: Application Of The Quantum Teaching Model To Improve Student Learning Outcomes In Enumeration Rules Material In Class XII MIA 1 SMA Negeri 1 Sirenja - Ramadhani, Lara Rahmi; Hasbi, Muh.; M, Bakri (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
This study aims to obtain a description of the application of the Quantum Teaching model to improve student learning outcomes on enumeration rules in class XII MIA 1 SMA Negeri 1 Sirenja. This research is a Classroom Action Research with the design of Kemmis and Mc Taggrat. This research was conducted in two cycles totaling 32 students. In cycle I classical learning completeness was 55.17% while cycle II was 65.62%. The results showed that through the application of the Quantum Teaching model, student learning outcomes improved by following the phases of the Quantum Teaching model, namely (1)enrolling, researchers providing apperception and motivation through powerpoint and video shows (cycle II), (2)experiencing, students working on worksheets with their groups and playing them. music as a sign of starting worksheets, (3) labeling, students make conclusions from the worksheets with their groups, (4) demonstrating, the researcher directs the students to discuss the rules of enumeration, (5)reviewing, the students convey the essence of the material they have learned, (6)celebrating, the researcher plays the game and gives awards to the students.